KESENJANGAN GENDER DAN KESETARAAN KETENAGAKERJAAN: SEBUAH TINJAUAN - Suryono Efendi (GoAcademica Research dan Publishing, 2018)
The purpose of this article is to discuss Employment Equity and many sub-issues including male domination in organizations, target groups, government policies, and quota systems. This study attempts to address the topic of whether equality in the mirror is only